THE IMPORTANCE OF RURAL TOURISM DEVELOPMENT IN THE SREM DISTRICT - Kosanović, Nada; Bartula, Mirjana; Karna, Mihajlo (Economics of Agriculture, 2024)
Contemporary rural business trends emphasize tourism’s vital role in holistic rural development, signaling forthcoming transformations. In the 21st century, rural tourism must adapt to evolving domestic and international demands, showcasing diverse aspects of rural life. Success in family farms will hinge on effective branding, market understanding, customer relations, and product quality. Methodologically, this study compares demographic and economic indicators across seven municipalities in the Srem District over three years, post-COVID-19. Findings reveal Srem’s rural tourism product lacks market positioning. To excel domestically, Srem must establish itself as a rural tourism hotspot, leveraging its unique attributes for competitive advantage. This entails integrating diverse offerings into a cohesive market presence, fostering spatial connectivity.